Bryoflora of Gallery Forest in Quirinópolis, Goiás State, Brazil - Herla Ferreira de Aquino; Isa Lucia de Morais Resende; Denilson Fernandes Peralta; Lucas Matheus da Rocha (Hoehnea)
ABSTRACT This study provides a survey of the bryophytes in gallery forest in the municipality of Quirinópolis, Goiás State, Brazil. Samples were collected monthly from April 2012 to July 2013. The substrate colonization and frequency of species were analyzed. The material was collected according to the usual procedures and is deposited at HerbJAR of UEG. We found 38 species of bryophytes (25 mosses and 13 liverworts). The richest families were Hypnaceae for mosses and Lejeuneaceae for liverworts, with five and seven species recorded, respectively. Isopterygium tenerum (Sw.) Mitt. was the most frequent species, and has a wide distribution in Brazil. Dicranodontium pulchroalare subsp. brasiliense (Herzog) J.-P.Frahm is a new record for the Cerrado, and Philonotis sphaericarpa (Hedw.) Brid., Lejeunea caulicalyx (Steph.) E. Reiner, and L. quinque-umbonata Spruce are new records for Goiás State.